Association Between Polymorphisms in Dopamine‐Related Genes and Orthopedic Pain Expression in a Chinese Elderly Population. Issue 2 (11th November 2018) - Chu, Che‐Sheng; Chu, Chin‐Liang; Liang, Chih‐Kuang; Lu, Ti; Lin, Yu‐Te; Chou, Ming‐Yueh; Chow, Philip Chik‐Keung
Abstract: Objectives: The dopaminergic pathway plays a vital role in pain expression. Here, our aim was to investigate the effects of polymorphisms in genes encoding the dopamine active transporter ( SLC6A3 ) and dopamine receptor D2 ( DRD2 ) on preoperative pain expression among patients preparing for orthopedic surgery. Methods: Chinese elderly patients scheduled for orthopedic surgery were enrolled. The VAS was used to evaluate pain intensity (score range 0 to 10; 0 = no pain; 10 = worst pain possible). Depressive symptoms were evaluated via the 15‐item Geriatric Depression Scale. DNA was isolated from venous blood samples, and single‐nucleotide polymorphisms of SLC6A3 and DRD2 were genotyped. Multiple linear regressions analyses were carried out to adjust the results for confounders. Results: A total of 294 patients with a mean age of 73.82 ± 8.03 years were enrolled in this study. After adjustment for confounders, rs393795 in SLC6A3 showed a significant association with preoperative VAS scores. Patients with the A/A genotype reported lower mean pain scores than did those with the A/C genotype ( P  =   0.026). Subsequent depression‐stratified analysis of rs6276 in DRD2 revealed that patients with the A/A genotype had higher pain scores than did those with the G/G genotype ( P  =   0.043). No associations were found for DRD2 rs6277 in the whole study population or depression‐stratified groups. Conclusion: Genetic variations in SLC6A3 and DRD2 may play an important role in pain expression among the elderly prior to orthopedic surgery.